Prevalence and correlates of coronary microvascular dysfunction in heart failure with preserved ejection fraction: PROMIS-HFpEF. (27th August 2018) - Shah, Sanjiv J; Lam, Carolyn S P; Svedlund, Sara; Saraste, Antti; Hage, Camilla; Tan, Ru-San; Beussink-Nelson, Lauren; Fermer, Maria Lagerström; Broberg, Malin A; Gan, Li-Ming; Lund, Lars H
Abstract: Aims: To date, clinical evidence of microvascular dysfunction in patients with heart failure (HF) with preserved ejection fraction (HFpEF) has been limited. We aimed to investigate the prevalence of coronary microvascular dysfunction (CMD) and its association with systemic endothelial dysfunction, HF severity, and myocardial dysfunction in a well defined, multi-centre HFpEF population. Methods and results: This prospective multinational multi-centre observational study enrolled patients fulfilling strict criteria for HFpEF according to current guidelines. Those with known unrevascularized macrovascular coronary artery disease (CAD) were excluded. Coronary flow reserve (CFR) was measured with adenosine stress transthoracic Doppler echocardiography. Systemic endothelial function [reactive hyperaemia index (RHI)] was measured by peripheral arterial tonometry. Among 202 patients with HFpEF, 151 [75% (95% confidence interval 69–81%)] had CMD (defined as CFR <2.5). Patients with CMD had a higher prevalence of current or prior smoking (70% vs. 43%; P = 0.0006) and atrial fibrillation (58% vs. 25%; P = 0.004) compared with those without CMD. Worse CFR was associated with higher urinary albumin-to-creatinine ratio (UACR) and NTproBNP, and lower RHI, tricuspid annular plane systolic excursion, and right ventricular (RV) free wall strain after adjustment for age, sex, body mass index, atrial fibrillation, diabetes, revascularized CAD, smoking, left ventricular mass, and study site ( P < 0.05 for all associations). Conclusions: PROMIS-HFpEF is the first prospective multi-centre, multinational study to demonstrate a high prevalence of CMD in HFpEF in the absence of unrevascularized macrovascular CAD, and to show its association with systemic endothelial dysfunction (RHI, UACR) as well as markers of HF severity (NTproBNP and RV dysfunction). Microvascular dysfunction may be a promising therapeutic target in HFpEF.